The role of bamboo, rattan & medicinal plants in mountain development: Proceedings of a workshop, 15-17 May 1996, Institute of Forestry, Pokhara, Nepal - Karki, M.; Rao, A.N.; Ramanatha Rao, V.; Williams, J.T. (1997)
These proceedings of the workshop held 15-17 May, 1996 in Pokhara, Nepal focus on the roles of three important non-timber forest products-bamboo, rattan and medicinal plant-in the development of mountain areas of the Hindu Kush-Himalaya and beyond. The scope of this workshop encompassed the whole range of ecological zones in the mountains and involved discussions on the environmental, socio-economic, and cultural value systems in integrated development with a specific focus on bamboo, rattan and medicinal plants. While we have some understanding of the present use of these keystone commodities, we also know that the increasing levels of exploitation are not sustainable and that rural communities benefit insufficiently from this exploitation. The workshop participants identified the policies and practices for improved management of these groups of plants that would contribute to environmental stability, conservation of the resources and enhanced utilization for increased incomes and other benefits to the poor mountain households of this region. Innovative mechanisms for improved resource management, processing and trade are required to tap the full potential of these versatile plants. We hope that the present document can play a role in further promoting collaboration and information exchange in the development of this group of plants.